Global agricultural trade and developing countries - Aksoy, M. Ataman; Beghin, John C.; World Bank. (Washington, D.C. : World Bank, 2005)
The studies analyze current policy regimes in key producing and consuming countries document the magnitude of these distortions and estimates the distributional impacts -winners and losers- of trade and domestic policy reforms. By bringing the key issues and findings together in one place, Global Agricultural Trade and Developing Countries aids policy makers and researchers, both in their approach to global negotiations and in evaluating their domestic policies on agriculture. This book also complements the recently published Agriculture and the WTO that focuses primarily on the agricultural issues within the context of the WTO negotiations.
Includes bibliographical references and index.
rpm 19/09/16
Loans
Keywords: Produce trade; International economic relations